Minimally processed guava fruits (Psidium guajava L.) - Durigan, J. F.; Mattiuz, B. H.; Lima, M. A.; Epiphanio, RDV; Biscegli, C. I. (International Society Horticultural Science, 2005)
'Paluma' guavas, after internal quality evaluation using magnetic resonance tomography, were used to produce fresh-cut product. Fruits were peeled or not, cut in halves and seed removed, and they were packaged in polystyrene trays covered with PVC film or in a PET container with a lid. These packages were stored for 12 days at 5 degrees C, 10 degrees C and ambient temperature (22.6 degrees C). Tomography evaluation verified that impacts produced internal bruising with loss of cellular integrity and liquefication of the placenta tissues. Compression was more evident on the pericarp and cutting promoted superficial deformation. Storage temperature affected the weight loss, with fruit packaged in the polystyrene tray having a greater weight loss. The peeling did not influence weight loss. Product stored at 5 degrees C and 10 degrees C for 8 days had low microbial growth (< 10(3) UFC.g(-1)) and no coliforms. Rapid spoilage and a short shelf life (3-4 days) occurred when the product was stored at ambient temperature. Peeling reduced ascorbic acid concentration and total soluble solids. Use of calcium to protect fresh-cut products was not efficient. Calcium absorption capacity of 'Pedro Sato' guava was tested using Ca-45. Fruits treated with 2% CaCl2, with or without the radioisotope, were divided in four layers (epicarp, mesocarp, endocarp and seed) and analyzed for the total and Ca-45 calcium. It was observed that the applied calcium remained in superficial layers of fruits, which was confirmed by autoradiography. Internal layers did not contain Ca-45, indicating that calcium was not distributed into different parts of the fruit.
Keywords: fresh-cut; magnetic resonance; tomography; calcium absorption; cold storage